Getting the best out of data for open access monograph presses: A case study of UCL Press. Issue 4 (9th July 2018) - Montgomery, Lucy; Neylon, Cameron; Ozaygen, Alkim; Leaver, Tama
Abstract : This study of UCL Press sought to identify the extent to which data available to open access (OA) monograph presses can be combined with low‐cost analysis tools to provide insight into development and strategy. An additional goal was identifying practical steps that monograph publishers can take to ensure that they make the most of the data they have access to. The project team carried out an analysis of downloaded figures from platforms providing access to UCL Press monograph titles, social media activity, and sales patterns. Patterns of engagement with the books were cross‐referenced against key marketing and dissemination events in order to identify relationships between marketing approaches and awareness or use of a title. This study shows that it is possible to gain valuable insights into the uses of OA books by collating and analysing usage and social media data. It also identifies a series of relatively straightforward steps that can be taken by presses to maximize the richness of the data captured. These include proactively gathering and storing data; providing best practice advice to those engaging in promotion, particularly when promotion is via social media; and making it easier to track specific efforts to publicize books by using tagged links.